Ophthalmic pharmaceutical clinical trials: design considerations. (May 2015) - Varner, Paul
Evidence-based medicine requires diligent literature review in order to assess the findings of published clinical reports. Sound experimental procedures, based on the Scientific Method are conducted with a consideration of several background factors underlying clinical trial research. A discussion of these underpinnings and other factors influencing clinical trial design as they apply to ophthalmic pharmaceutical trials is provided, with the intent of providing a means of applying these considerations to literature review.